Country Partnership Framework for Kingdom of Cambodia for the Period of FY2019-2023 - World Bank Group (World Bank, Washington, DC, 2019)
Cambodia has undergone a significant economic transition, reaching lower middle-income country status in 2015, and now is poised to enter a new stage of development. The World Bank Group’s relationship with Cambodia has matured significantly since the implementation of the FY16-17 Country Engagement Note. The WBG Country Partnership Framework for FY19-23 supports Cambodia’s progression to the next stage of its development and reflects the evolution of the WBG’s engagement in the country.